Effect of feeding sesame (Sesamum indicum) seed on reproductive events in post-partum Murrah buffaloes – A pilot study (Indian Journal of Animal Production and Management, 2024)
The present study was carried out to evaluate a traditional practice on buffalo reproductive events during postpartum period. Eighteen Murrah buffaloes’ parity ranged between 2nd and 9th were included in the study. A mixture of 250 g sesame and 250 g jaggery made as an electuary and fed to the treatment group (Sesame fed group) of buffaloes, the first dose of this electuary was fed within 30 min of calving and continued daily once till eighth day post-partum. The control group was given 250 g jaggery and 350 g of compound feed to ensure equal quantity of protein and energy to both the groups. The results indicate that buffaloes which were fed sesame within 30 min post-partum have expelled fetal membranes significantly (p
Keywords: Buffalo; Lochia; Post-partum period; Sesame; Uterine involution